The Pocket Essential Horror Films / Odell, Colin ; Blanc, Michelle Le - Odell, Colin
Er, normally at this stage we thank lots of people for lending us resource materi-als but we seem to be such reprobates that our collection spoke for itself. Thanks to our parents who thoroughly disapprove of all the nasty films we watch and Marc, who thoroughly approves of the films we watch. Thanks also to Paul Duncan, Steve Holland and Elizabeth Billinger. A big hello to Tony, Andy, Lizbeth, Paul, Gary, Kay, Elyse and Jim on the Camera Obscurer web bounce. To Flo and Mo, who stalk the fields of Alderney and finally to Alice, who tortures and kills small furry creatures and leaves their remains on the carpet...